Analisis Tipologi Saham Syariah Di Bursa Efek Indonesia Berdasarkan Nilai Return Dan Resiko (Value At Risk) Pasca Krisis Global 2008 - Qudratullah, Mohammad Farhan (UIN Sunan Kalijaga Yogyakarta, 2012)
Since the signed memorandum of understanding between BAPEPAM with Dewan Syariah Nasional-Majelis Ulama Indonesia (DSN-MUI) on the principle of Islamic capital market in 2003, the Islamic capital market in Indonesia has developed significantly. In each investment, including Islamic capital market investment, there are 2 (two) fundamental things that always accompany it, the return and risks. This paper discusses the analysis of return and risk of sharia stocks that always go in Jakarta Islamic Index (JII) after the global crisis in 2008, risk analysis tools using Value at risk (VaR) approach to model the Generalized Autoregressive ConditionalÂ Heteroscedastic (GARCH), then proceed with the analysis of the typology to determine the characteristics of these stocks. The results that shares sharia can be grouped into 4 (four) :Â 6 (six) shares entering the low return and low risk (TLKM, UNVR, SMGR, AALI, ELSA, and SGRO), 3 (three ) shares into group of low-return but high risk (INCO, ANTM, and TINS), 3 (three) shares enter the group of low risk but high return (PTBA, LSIP, and KLBF), and 4 (four) shares enter the group high return but high risk (ITMG, ASII, INTP, and BMTR).